A large deformation finite element investigation of pile group installations with consideration of intervening consolidation. (July 2021) - Yi, Jiang Tao; Liu, Fei; Zhang, Tai Bin; Yao, Kai; Zhen, Guo
Highlights: We perform coupled effective stress large deformation finite element analyses of pile group installations with consideration of intervening consolidation. Intervening consolidation condition clearly affects pore pressure generation and accumulation, soil strength improvement, set-up effects on pile shaft and bearing resistances. Assuming soil remains at in-situ strength state may be non-conservative for the estimation of short-term pile capacity. Timely dissipation of excess pore pressure amongst neighboring pile installations is beneficial notably for the development of pile base resistance. Abstract: Piles are usually installed in both onshore and offshore sites to transit the structural loads through soft or loose soil layers to competent soil strata. Although the installation of a single pile is usually considered to be undrained, consolidation may take place during the installations of multiple piles, especially in the pauses between neighboring pile installations i.e. intervening consolidation. To date, the role that the intervening consolidation can play in affecting soil stress and strength states as well as set-up of pile capacities remains largely unclear. This article reports effective stress large deformation analyses of pile group installations with consideration of intervening consolidation. The results indicate pore pressure generation and accumulation, soil strength improvement, set-up effects on pile shaft and bearing resistances are clearly affected by intervening consolidation condition. It may be non-conservative to assume soil remains at in-situ strength state for the estimation of short-term pile capacity in design practice, if no intervening consolidation takes place. Timely dissipation of excess pore pressure amongst neighboring pile installations is beneficial notably for development of pile base resistances. The present findings are likely helpful in deepening the understanding of intervening consolidation and facilitating the incorporation of set-up effects into pile design practices.